Biochemical characterization of the Escherichia coli surfaceome: a focus on type I fimbriae and flagella - Devon W. Kavanaugh; Adeline Sivignon; Yannick Rossez; Zina Chouit; Christophe Chambon; Christophe Chambon; Louane Béal; Mathilde Bonnet; Michel Hébraud; Michel Hébraud; Yann Guérardel; Hang Thi Thu Nguyen; et al. (Frontiers in Microbiology)
The Escherichia coli surfaceome consists mainly of the large surface organelles expressed by the organism to navigate and interact with the surrounding environment. The current study focuses on type I fimbriae and flagella. These large polymeric surface organelles are composed of hundreds to thousands of subunits, with their large size often preventing them from being studied in their native form. Recent studies are accumulating which demonstrate the glycosylation of surface proteins or virulence factors in pathogens, including E. coli. Using biochemical and glycobiological techniques, including biotin-hydrazide labeling of glycans and chemical and glycosidase treatments, we demonstrate (i) the presence of a well-defined and chemically resistant FimA oligomer in several strains of pathogenic and non-pathogenic E. coli, (ii) the major subunit of type I fimbriae, FimA, in pathogenic and laboratory strains is recognized by concanavalin A, (iii) standard methods to remove N-glycans (PNGase F) or a broad-specificity mannosidase fail to remove the glycan structure, despite the treatments resulting in altered migration in SDS-PAGE, (iv) PNGase F treatment results in a novel 32 kDa band recognized by anti-FliC antiserum. While the exact identity of the glycan(s) and their site of attachment currently elude detection by conventional glycomics/glycoproteomics, the current findings highlight a potential additional layer of complexity of the surface (glyco) proteome of the commensal or adhesive and invasive E. coli strains studied.